Hydrological change: Towards a consistent approach to assess changes on both floods and droughts. (January 2018) - Quesada-Montano, Beatriz; Di Baldassarre, Giuliano; Rangecroft, Sally; Van Loon, Anne F.
Highlights: We posit that consistent approaches are needed to assess changes on both hydrological extremes, i.e. floods and droughts. We propose a method based on the theory of runs and threshold levels. We show an example application to the Po River, Italy. Abstract: Several studies have found that the frequency, magnitude and spatio-temporal distribution of droughts and floods have significantly increased in many regions of the world. Yet, most of the methods used in detecting trends in hydrological extremes 1) focus on either floods or droughts, and/or 2) base their assessment on characteristics that, even though useful for trend identification, cannot be directly used in decision making, e.g. integrated water resources management and disaster risk reduction. In this paper, we first discuss the need for a consistent approach to assess changes on both floods and droughts, and then propose a method based on the theory of runs and threshold levels. Flood and drought changes were assessed in terms of frequency, length and surplus/deficit volumes. This paper also presents an example application using streamflow data from two hydrometric stations along the Po River basin (Italy), Piacenza and Pontelagoscuro, and then discuss opportunities and challenges of the proposed method.